The Hippo signaling pathway modulates pancreatic tissue homeostasis - Xiaoyan Wang; Jiajing Du; Haiyun Li; Zhiwei Cao; Zhonghua Cheng; Zuoyun Wang (Cell Death Discovery)
Abstract The Hippo signaling pathway, a highly conserved signaling cascade from Drosophila to mammals, plays a critical role in mammals in regulating cell proliferation, senescence and apoptosis. In the pancreas, this pathway has emerged as a key regulator in various processes, including development, cell fate determination, and regeneration following injury. Consequently, aberrant the Hippo signaling pathway disrupts pancreatic tissue homeostasis, leading to uncontrolled cell proliferation, oncogenic transformation, and the subsequent development of pancreatic diseases. In this review, we comprehensively summarize the multifaceted roles of the Hippo signaling pathway in both physiological and pathological aspects of the pancreas, such as pancreas development, pancreatitis, pancreatic ductal adenocarcinoma and diabetes. Furthermore, we highlight the potential mechanisms and new therapies targeting the Hippo signaling pathway in pancreatic diseases, which helps to address unresolved issues in research.